PERANCANGAN GEDUNG KANTOR SEWA BORNEO KHATULISTIWA 4 LANTAI DENGAN MENGGUNAKAN BETON BERTULANG JALAN JENDERAL AHMAD YANI KOTA PONTIANAK: PERANCANGAN GEDUNG KANTOR SEWA BORNEO KHATULISTIWA 4 LANTAI DENGAN MENGGUNAKAN BETON BERTULANG JALAN JENDERAL AHMAD YANI KOTA PONTIANAK - yazid, faiz; Syahrani, Deny; Konstatinus, ayub; kurnadi, riksa (Jurusan Teknik Sipil Polnep, 2022)
The office is a place for business people to carry out their activities. The office is the main supporter of activitiesfor business people, because in addition to being a place for their activities, the office can also be an image orclass for business because business is a commercial activity. using a reinforced concrete structure and planned 4floors. In designing the building, the priority is the strength of the office building structure so as not to cause aloss and also loss of life with the design of the building using the Intermediate Moment Bearing Frame System.The rental office building is designed to be strong against several combinations of loads such as dead loads, liveloads, wind loads and earthquake loads. This method of calculating the Equatorial Borneo rental office buildingcollects land data and image data as the basis for the design. In the depiction using the AutoCad program andthe engineering analysis using the SAP 2000 3D program, as well as the calculation of building structuresreferring to SNI 03-2847-2013 for concrete structures, SNI 1727-2013 regarding minimum loads and LoadingPlanning for Houses and Buildings (PPURG) 1987 and SNI 1729-2019 for earthquake-resistant buildingstructures. The results of the structural design are the thickness of the ground floor slabs to the 4th floor and Dakhas a plate thickness of 100 mm 6, the dimensions of the main beam structure are 30 x 60 cm with D16 mainreinforcement and begel reinforcement 8-200 mm child beams 20 x 40 cm D16 main reinforcement as well asbegel reinforcement 8-150 mm. Column dimensions are 50 x 50 cm D16 principal reinforcement and 10-200 mmbegel reinforcement using 300x 300 mm piles with 3.3 x 3.3 pile caps with main reinforcement and stirrupreinforcement with a depth of 27 m. From the results of the design and calculation of the structure of theEquatorial Borneo rental office building, it can be a reference for analysis purposes in the design of the nextbuilding.